A variety and morphologic-physiological properties of the yeast living in conditions of various vertical zoning - E. S. Magomedova; D. A. Abdullabekova; Sh. A. Abramov (Юг России: экология, развитие, 2015)
A taxonomic composition and morphophysiologic properties of grapecolous and fruitcolous yeast are studied in conditions of different vertical zone. It is revealed a genesic diversity of populations and itsdecreasing in the foothills. In all height marks there is found the availabitity of biological active stocks.